Despair Will Hold You Prisoner, Hope Will Set You Free: Hope and Meaning Among Released Prisoners - Ṿignansḳi, Efrat (The prison journal, 2018)
The current study examines the self-image and worldviews of 10 released prisoners in Israel through narrative analysis of their life stories, including past and present periods in their lives and future aspirations. The findings reveal a chaotic past perceived as lacking meaning, hope, and clear boundaries while being devoid of choice. Prison is considered a turning point, and attitudes after release change toward choice, life meaning, and a hopeful future. The discussion addresses these themes, and the important variables of hope and life meaning in generating changed goals and rehabilitation.